Novel Heterostructure of CdSe Nanobridge on ZnO Nanorods: Cd‐Carboxyl‐RGO‐Assisted Synthesis and Enhanced Photoelectrochemical Efficiency. Issue 12 (7th March 2016) - Zhang, Zhuo; Choi, Mingi; Baek, Minki; Yong, Kijung
Abstract : Photoelectrochemical (PEC) hydrogen generation is a green and effective strategy for addressing energy crises. In this study, a CdSe heteronanobridge (HNB) structure is fabricated as PEC photoanode via a hydrothermal method. The "pier" is built using ZnO nanorods (NRs) decorated with CdSe nanoparticles (NPs), and the "bridge" is constructed using CdSe nanowire covered by an reduced graphene oxide (RGO) layer and cross‐linked with ZnO NRs. The formation of the CdSe NBs is ascribed to the passivation of the CdSe nonpolar surface with an RGO layer by the formation of Cd‐carboxyl‐RGO bond in alkaline solution, which directs the preferential growth of CdSe along c‐axis. Additionally, despite etching the functionalized RGO with HAuCl4 solution, CdSe NBs decorated with Au NPs are also synthesized as another heteronanostructure. This study demonstrates that the photoconversion of the CdSe hetero‐NBs can be enhanced via the type II cascade band alignment of CdSe and ZnO and efficient charge transfer through net‐like bridge structures. Moreover, the Cd‐carboxyl‐RGO layer and Au NPs can improve the electron lifetime of the CdSe NBs by suppressing electron–hole recombination. Overall, CdSe hetero‐NBs with increased PEC efficiency represent a promising photoanode material, and the synthesis route can be used to build highly networked heteronanostructures of other materials. Abstract : CdSe heteronanobridges constructed by using CdSe nanowire covered with an reduced graphene oxide (RGO) layer and decorated with Au nanoparticles are demonstrated as highly efficient photoelectrochemical anode materials, respectively. The photoconversion is enhanced by type‐II cascade band alignment of CdSe and ZnO, and efficient charge transfer through net‐like bridge structures, as well as suppressed electron–hole recombination via Cd‐carboxyl‐RGO layer or Au nanoparticles.